2002
DOI: 10.1128/iai.70.9.5299-5303.2002
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejunifrom Patients with Guillain-Barré Syndrome Preferentially Expresses a GD1a-Like Epitope

Abstract: GM 1 -and GD 1a -like ganglioside mimicry in Campylobacter jejuni lipooligosaccharide (LOS) is considered to be involved in the pathogenesis of Campylobacter-induced Guillain-Barré syndrome (GBS). Compared with gastroenteritis-related isolates, GBS-related C. jejuni isolates were strongly associated with the expression of GD 1a -like mimicry. The presence of a few genes involved in LOS ganglioside mimicry, cst-II, cgtA, and cgtB, was also associated with GBS-related strains. GD 1a -like epitope expression may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 40 publications
3
74
1
Order By: Relevance
“…We surveyed 16 GBS-associated isolates and found that 14 were positive for class A1 products, whereas the other 2 isolates were positive for ganglioside-associated classes A2 and C (Table 5). This is consistent with a study by Nachamkin et al (21), who previously demonstrated a strong association of cst-II (orf7a,b), cgtA (orf5), and cgtB (orf6) with GBS isolates. It should be noted that most of the GBS-associated strains in this study (12 of 16 GBS strains) were HS:19 or HS:41, which have been shown to be genetically clonal (13,28).…”
Section: Los Classes Of Isolates From Clinical and Environmental Soursupporting
confidence: 82%
“…We surveyed 16 GBS-associated isolates and found that 14 were positive for class A1 products, whereas the other 2 isolates were positive for ganglioside-associated classes A2 and C (Table 5). This is consistent with a study by Nachamkin et al (21), who previously demonstrated a strong association of cst-II (orf7a,b), cgtA (orf5), and cgtB (orf6) with GBS isolates. It should be noted that most of the GBS-associated strains in this study (12 of 16 GBS strains) were HS:19 or HS:41, which have been shown to be genetically clonal (13,28).…”
Section: Los Classes Of Isolates From Clinical and Environmental Soursupporting
confidence: 82%
“…Firstly, not all GBS-associated C. jejuni strains express GM1 mimics, implicating other LPS structures, particularly those with multiple sialic acid groups. [35][36][37] Moreover, a small proportion of GBS-associated strains do not express sialated ganglioside mimics at all. 38 Secondly, not all C. jejuni serotypes known to express GM1-like LPS have been associated with GBS.…”
Section: Receptor Mimic Probiotics For Etec Infectionsmentioning
confidence: 99%
“…Analysis of the genes involved in the synthesis of ganglioside-like LOS may be of great importance for clarifying which C. jejuni strains involved in the pathogenesis of GBS/FS. The presence of LOS synthesis genes (cst-II, cgtA, and cgtB) is associated statistically with GBS-related isolates (20). GQ1b ganglioside is a target molecule for IgG antibody in FS (3), and all C. jejuni strains studied that bore the GQ1b epitope had cst-II, an essential gene for production of GQ1b-like LOS (27).…”
Section: Vol 43 2005mentioning
confidence: 99%